PROBLEMATIKA PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA KORUPSI STUDI KASUS MEGA KORUPSI PERTAMINA DAN IMPLEMENTASI RESTORATIVE JUSTICE - Juhana Nuryana; Siti Humulhaer; Muslimin; Rifqi Syifa’ul Qolbi (CV. Lafadz Jaya, 2026)
The nature of corruption in Indonesia has undergone a significant transformation from individual corruption to systemic corruption involving corporations as the main actors. This paper analyses the issue of corporate criminal liability in the 2025 PT Pertamina (Persero) mega-corruption case, which caused losses to the state amounting to Rp193.7 trillion, and examines the concept of restorative justice as an alternative means of resolving corruption cases. Using a normative legal research method with a legislative, conceptual and case-based approach, this study finds that the existing legal framework has weaknesses in holding corporations accountable as perpetrators of systemic corruption. Constitutional Court Decision No. 142/PUU-XXIII/2024 and developments in the Anti-Corruption Law indicate the need for a normative reconstruction of corporate criminal liability. On the other hand, the application of restorative justice in corruption remains controversial given the extraordinary nature of corruption, which demands a balanced repressive-preventive approach. The research findings recommend the regulation of illicit enrichment and non-conviction-based asset forfeiture as effective legal instruments to maximise the recovery of state assets.